2021
DOI: 10.1051/0004-6361/202039364
|View full text |Cite
|
Sign up to set email alerts
|

Optical-to-NIR magnitude measurements of the Starlink LEO Darksat satellite and effectiveness of the darkening treatment

Abstract: Aims. We aim to measure the Sloan r′, Sloan i′, J, and Ks magnitudes of Starlink’s STARLINK-1130 (Darksat) and STARLINK-1113 low Earth orbit (LEO) communication satellites and determine the effectiveness of the Darksat darkening treatment from the optical to the near-infrared (NIR). Methods. Four observations of Starlink’s LEO communication satellites, Darksat and STARLINK-1113, were conducted on two nights with two telescopes. The Chakana 0.6 m telescope at the Ckoirama observatory (Chile) observed both satel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…We, unfortunately, cannot confirm that the satellites indicated as Starlink-Vs do indeed have visors or that the visors are correctly deployed. Starlink-1436 is the first visorsat (e.g., see discussion in Tregloan-Reed et al 2021), placed on orbit as a test case and widely discussed on social media. Additional Starlink satellites were launched without visors until the tenth Starlink mission, which according to SpaceX (SpaceX 2020), included deployable visors for all 57 Starlink satellites on board the 6 August 2020 Falcon 9 launch.…”
Section: Target Selection and Observing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We, unfortunately, cannot confirm that the satellites indicated as Starlink-Vs do indeed have visors or that the visors are correctly deployed. Starlink-1436 is the first visorsat (e.g., see discussion in Tregloan-Reed et al 2021), placed on orbit as a test case and widely discussed on social media. Additional Starlink satellites were launched without visors until the tenth Starlink mission, which according to SpaceX (SpaceX 2020), included deployable visors for all 57 Starlink satellites on board the 6 August 2020 Falcon 9 launch.…”
Section: Target Selection and Observing Methodsmentioning
confidence: 99%
“…Several groups have reported on LEO satellite magnitudes under various conditions (Tyson et al 2020;Tregloan-Reed et al 2021;Mallama 2021a). This includes efforts to focus on specific satellites to assess mitigation attempts, such as 'DarkSat' and 'Visorsats', representing albedo and reflection modifications, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that a) the reduction in brightness for DarkSat was 50.8% ± 3.5%, b) the brightness magnitude of DarkSat (6.10 magnitudes) was still within the range of the naked-eye limiting magnitude of an experienced observer (Bortle, 2001) and c) DarkSat was still brighter than the limiting magnitude of 7 that has been recommended to minimise unwanted effects in sensitive astronomical cameras (Walker et al, 2020;IAU 2020). Subsequent observations of these satellites were conducted in various spectral bands to assess their brightness and the effectiveness of the darkening treatment used in DarkSat, in various astronomical spectral bands from visible to near-infrared (Tregloan-Reed et al, 2021). The results of these observations, conducted using the Chakana telescope (Char et al, 2016) and VIRCAM (Emerson, McPherson & Sutherland, 2006;Dalton et al, 2006) on the VISTA telescope, are summarised in Figure 4.…”
Section: Satellite Observationsmentioning
confidence: 99%
“…Most of the current efforts have focussed on obtaining (multi-colour) broadband flux lightcurves (e.g. Horiuchi et al, 2020;Tregloan-Reed et al, 2021;Mróz et al, 2022), and basic models have been created to evaluate expected brightness as a function of sun-observer-satellite angle (e.g. Hainaut & Williams, 2020;Mallama, 2020;Cole, 2021;Bassa et al, 2022;Lawler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%